Penerapan Dan Penggunaan Teknologi Masa Depan Dalam Novel Matahari (Unedited Version) Karya Tere Liye - Nur Ardiansyah, Taufik; Dwi Kurniawan, Eva (Shofanah Media Berkah, 2024)
This study aims to examine the role and use of modern technology in the future as depicted in Tere Liye's novel